Social networking in tumor cell communities is associated with increased aggressiveness. Issue 1 (2nd January 2016) - Lodillinsky, Catalina; Podsypanina, Katrina; Chavrier, Philippe
ABSTRACT: Extracellular vesicles (EVs) are lipid-bilayer-enclosed vesicles that contain proteins, lipids and nucleic acids. EVs produced by cells from healthy tissues circulate in the blood and body fluids, and can be taken up by unrelated cells. As they have the capacity to transfer cargo proteins, lipids and nucleic acids (mostly mRNAs and miRNAs) between different cells in the body, EVs are emerging as mediators of intercellular communication that could modulate cell behavior, tissue homeostasis and regulation of physiological functions. EV-mediated cell-cell communications are also proposed to play a role in disease, for example, cancer, where they could contribute to transfer of traits required for tumor progression and metastasis. However, direct evidence for EV-mediated mRNA transfer to individual cells and for its biological consequences in vivo has been missing until recently. Recent studies have reported elegant experiments using genetic tracing with the Cre recombinase system and intravital imaging that visualize and quantify functional transfer of mRNA mediated by EVs in the context of cancer and metastasis.